2011
DOI: 10.1016/j.virol.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of low pathogenicity H5N1 and H7N3 influenza A virus isolates recovered from sentinel, free flying, wild mallards at one study site during 2006

Abstract: From August 2-October 11, 2006, clusters of low pathogenicity (LP) North American lineage H5N1 and H7N3 avian influenza A viruses (AIV), and other subtypes, were recovered from free-flying, resident, wild mallards used as sentinels at one site. The antigenic subtypes, pathogenicity potential, and Sanger sequencing of the isolates determined the H5N1 and H7N3 isolates were only recovered from samples collected on 8/2/2006 and 9/8/2006, respectively. However, subsequent efforts using next-generation sequencing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Earlier studies suggested that AIV exhibits a strongly spatially structured population in North America, with relatively infrequent gene flow among localities and especially between those that are spatially distant or belong to different flyways using phylogeographic analysis [27]. This hypothesis was supported by studies showed that AIV isolates from mallard were linked by migration between sites in central Canada and Maryland but limited reassortment occurred along the inter-migratory flyway routes [28]. However, more recently, the opposite was seen in a another study, which emphasized that the long-term persistence of the influenza A virus gene pool in North American wild birds may be independent of migratory flyways, and the short-term evolutionary consequences of these ecological barriers may be rapidly erased by East-West virus migration [29].…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies suggested that AIV exhibits a strongly spatially structured population in North America, with relatively infrequent gene flow among localities and especially between those that are spatially distant or belong to different flyways using phylogeographic analysis [27]. This hypothesis was supported by studies showed that AIV isolates from mallard were linked by migration between sites in central Canada and Maryland but limited reassortment occurred along the inter-migratory flyway routes [28]. However, more recently, the opposite was seen in a another study, which emphasized that the long-term persistence of the influenza A virus gene pool in North American wild birds may be independent of migratory flyways, and the short-term evolutionary consequences of these ecological barriers may be rapidly erased by East-West virus migration [29].…”
Section: Discussionmentioning
confidence: 92%
“…The frequent reassortment and rapid movement of H7 influenza viruses within this population necessitate continued surveillance of this virus subtype in both wild and domestic birds (54). The continued assessment of H7 viruses detected during routine surveillance, poultry outbreaks, and human infections is critical to both assess the pandemic potential of these strains in humans and characterize laboratory mammalian models suited to examine the efficacy and cross-reactivity of candidate H7 vaccines against viruses within this subtype (34,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…KC703328 to KC703335), is in contrast with other viruses detected on Argentinian coasts, which have a diversity of segment similarities to other South American, North American and even Eurasian lineages (Pereda et al, 2008;Xu et al, 2012). These apparent differences among Pacific and Atlantic South American reports require more isolates for establishing distribution patterns, such as those described in North America where rapid temporal and geographical movements of AI viruses and virus gene segments have been seen across migratory flyways (Chen and Holmes, 2009;Dugan et al, 2011).…”
mentioning
confidence: 86%